A Phase 2 Clinical Trial of Combination Nivolumab, Ipilimumab, and Paclitaxel in Patients With Untreated Metastatic NSCLC: The OPTIMAL Trial - Jeffrey M. Clarke, MD; Lin Gu, MS; Xiaofei F. Wang, PhD; Thomas E. Stinchcombe, MD; Marvaretta M. Stevenson, MD; Sundhar Ramalingam, MD; Afreen Shariff, MD; Jennifer Garst, MD; Andrew B. Nixon, PhD; Scott J. Antonia, MD; Jeffrey Crawford, MD; Neal E. Ready, MD, PhD (JTO Clinical and Research Reports, 2022)
Introduction: Most patients with advanced NSCLC will experience disease progression and death within 2 years. Novel approaches are needed to improve outcomes. Methods: We conducted an open-label, nonrandomized, phase 2 trial in patients with treatment-naive, advanced NSCLC to assess the safety and efficacy of nivolumab 360 mg every 3 weeks, ipilimumab 1 mg/kg every 6 weeks, and four to six cycles of paclitaxel 80 mg/m2 on days 1 and 8 of every 21-day treatment. The primary end point of the study was median progression-free survival (PFS), with secondary end points of safety, objective response rate, and median overall survival (OS). Results: A total of 46 patients underwent consent and received treatment. The median age was 66 (range: 48–82) years, most had adenocarcinoma (63%), and 50% (23) had programmed death-ligand 1 greater than or equal to 1%. The median follow-up on the study as of October 2021 was 19 months. The primary end point of median PFS was 9.4 months (95% confidence interval [CI]: 5.9–16.6) in all patients regardless of programmed death-ligand 1 expression. The objective response rate for patients in the study was 47.8% (95% CI: 33.4–62.3). The 12-month OS rate was 69.5% (95% CI: 53%–81%), and median OS was not yet reached. Treatment-related grade greater than or equal to 3 adverse events was found in 54.3% of the patients. Conclusions: The toxicity observed was consistent with other reported chemo-immunotherapeutic combinations and was manageable. The primary end point of exceeding median PFS of 9 months was achieved with nivolumab, ipilimumab, and weekly paclitaxel and should be evaluated further in a randomized trial.